Criminal economies, extractivism and intertwined accumulation: a multiscale analysis of the new Latin American scenarios - Terán-Mantovani, Emiliano (2024)
This article examines the new scenarios, formats and dimensions of crime in extractivism in Latin America, from a critical perspective, with a combination of economics/political ecology. An analysis of the intertwining dynamics that occur between the legal/formal aspects, the dispossession policies that are promoted from the spheres of power and the illicit/criminal economies is presented. This prism allows us to highlight the weight of these economies in the composition of extractivism, as well as analyze the evolution and development of the dynamics of legal/illegal accumulation throughout the Latin American historical process. In this sense, the article briefly highlights the historicity of said relationship to later examine characteristics and trends of the current economy/political ecology of extractivism. From a multi-scalar analysis we observe three complementary levels: a) Illicit/criminal extractions of natural resources, b) Intertwined illicit flows of commodities and c) New statehoods and hybrid governances. The hidden hybridizations that, from financial, fiscal, logistical, business and state spheres, enable and strengthen these violent extractions and illicit flows of natural resources are highlighted. At the same time, the analysis seeks to expand and strengthen the conceptualizations of extractivism.